Жертвоприношения в Тейшебайни (УКН 448). Из общественной истории Урарту - Дьяконов, И.M. (1988)
Diakonoff, I.M. Sacrifices in Teišebaini (UKN 448). From the Social Life in Urartu; English summary p.213-214